Pengaruh Pendapatan Asli Daerah, Surplus/Defisit Anggaran, dan Dana Alokasi Umum Terhadap Pinjaman Daerah di Provinsi Sumatera Selatan - Hilda Salsabila; Kartika Rachma Sari; Henny Yulsiati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to evaluate the results of the analysis of the influence of local revenue, budget surplus/deficit and general allocation funds on regional loans in South Sumatra Province. The sampling method in this study is using saturated sampling. This study uses secondary data as information. This study uses panel data regression assisted by the Econometric views (Eviews) version 12 program. The results of this study show the results of the t-test that the surplus/deficit has a negative and significant effect on regional loans, general allocation funds have a positive and significant effect on regional loans. The results of the F test show that local revenue, budget surplus/deficit, and general allocation funds have a joint and significant effect on regional loans.